Inhibition of the severe acute respiratory syndrome 3CL protease by peptidomimetic α,β-unsaturated esters - Shie, Jiun-Jie (Bioorg Med Chem, 2005)
The proteolytic processing of polyproteins by the 3CL protease of severe acute respiratory syndrome coronavirus is essential for the viral propagation. A series of tripeptide α,β-unsaturated esters and ketomethylene isosteres, including AG7088, are synthesized and assayed to target the 3CL protease. Though AG7088 is inactive (IC(50) > 100 μM), the ketomethylene isosteres and tripeptide α,β-unsaturated esters containing both P1 and P2 phenylalanine residues show modest inhibitory activity (IC(50) = 11–39 μM). The Phe-Phe dipeptide inhibitors 18a–e are designed on the basis of computer modeling of the enzyme–inhibitor complex. The most potent inhibitor 18c with an inhibition constant of 0.52 μM is obtained by condensation of the Phe-Phe dipeptide α,β-unsaturated ester with 4-(dimethylamino)cinnamic acid. The cell-based assays also indicate that 18c is a nontoxic anti-SARS agent with an EC(50) value of 0.18 μM.